[PP.19.29] DETERMINANTS OF EARLY VASCULAR AGEING: A MULTIVARIATE ANALYSIS. (September 2017) - Antza, C.; Doundoulakis, I.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of the study was to identify determinants of early vascular aging. Design and method: 278 consecutive subjects (47.5% male) aged 47.1 ± 22.9 years were included in the study. Subjects were never treated before for hypertension. All subjects underwent 24h-ABPM on a usual working day. Pulse wave velocity (PWV) was measured after 15 minutes of rest in the supine position. PWV was calculated as the transit time of the arterial pulse along the carotid-femoral distance divided with the distance measured directly and modified according the guidelines. Early vascular aging (EVA) was calculated using the age and the PWV values, according the guidelines. Results: In the univariate analysis, EVA was correlated with age, gender, body mass index (BMI), clinic SBP, clinic DBP, 24 h average of SBP, 24 h average of DBP, LDL levels and e-GFR (p < 0.05 for all), but not with uric acid. However, in the multiple linear regression model, only e-GFR, clinic DBP, 24 h average of SBP and 24 h average of DBP (p < 0.05 for all) remained significant predictors of EVA, even after adjustment for other factors. Conclusions: Kidney function, clinic DBP, 24 h systolic BP and 24 h diastolic BP were found to be statistically significant determinants of early vascular aging. This result shows the importance of establishing 24h-ABPM in the everyday clinical practice, as a determinant of early vascular aging.